1992
DOI: 10.1007/bf01954124
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the short arm of the X chromosome: A hereditary form of Turner syndrome

Abstract: In the mothers of two girls with Turner syndrome due to a deletion of the short arm of an X chromosome, the same chromosomal anomaly was detected. Both mothers and daughters had short stature but normal pubertal development. Short parents and normal pubertal development do not exclude Turner syndrome in a girl with small stature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…According to Therman and Susman (22), ovarian dysgenesis was seen in 91 % of patients with 45,X and in 65 % of patients with 46,X,del(Xp). In fact, there have been some reports concerning spontaneous puberty and (15)(16)(17)(20)(21)(22)(23)(24). However, only a few cases have been reported in which Xp deletion was transmitted from a mother to her daughter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Therman and Susman (22), ovarian dysgenesis was seen in 91 % of patients with 45,X and in 65 % of patients with 46,X,del(Xp). In fact, there have been some reports concerning spontaneous puberty and (15)(16)(17)(20)(21)(22)(23)(24). However, only a few cases have been reported in which Xp deletion was transmitted from a mother to her daughter.…”
Section: Discussionmentioning
confidence: 99%
“…In 1982, they reported another fertile woman with del(X)(p1106) who gave birth to a normal boy after two abortions (16). Massa et al (20) reported 2 pairs of mothers and their daughters with short arm deletion of the X chromosome. The karyotype of the 1st pair was del(X)(p211) and the second had del(X)(p114).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first cases of hereditary TS in women with different Xp deletions were published more than three decades ago [2,3]. As a result of this knowledge, the karyotyping of mothers of girls with Xp deletion has been recommended [4], which has led to the identification of additional cases of familial TS [5,6,7,8]. However, the transmission of TS in more than two sequential generations has rarely been reported [9].…”
Section: Introductionmentioning
confidence: 99%